THE AGRARIAN CONFLICTS IN CASTILLA DURING THE EIGHTEENTH CENTURY. THE EXAMPLE OF THE MANCHA ORIENTAL - Cózar Gutiérrez, Ramón (Revista de Historia Social y de las Mentalidades, 2011)
For a long time the historiography has represented the eighteenth-century Spain as an idyllic paradise where concord and unimportant facts prevailed. Far from being true, the situation lived in Spain was marked by a social conflict that can not be ignored. In this article we want to reinforce this idea, noting all the conflicting facts that occurred in La Mancha of Albacete in the years 1765, following the promulgation of the Royal Pragmatic liberalization of trade in grains, and 1766, where the climate of tension between generally favored by the mutiny in Madrid, two provincial riots that occupy an important place in Spanish history: Tobarra and Liétor. The first, being the first case of rebellion after the 1766 riot in Madrid, while the second has been considered by some authors as a representative of the finest examples of nineteenth century social unrest. We hope this study can contribute in some way to a better understanding of the social conflict in eighteenth-century Spain in general and in particular La Mancha Oriental.